Development of Education Districts in the Strategy of Strengthening the Axiological Foundations of the Russian Education Space - A. Yu. Belogurov; E. V. Voevoda; M. I. Inozemtsev; E. A. Romanova; N. I. Khokhlova (Высшее образование в России)
The article presents an analysis of the specific features of the socio-cultural modernization of education in contemporary Russia and the methodology of the development of the ethno-regional education systems against the background of strengthening the unified education space of Russia. Special attention is paid to the consideration of the strategy of the development of education districts of contemporary Russia as the foundation for building the government vertical of state management in the field of education.As part of the development of organizational and pedagogical resources of risk management of the gap between the scientific and education space of the country, the authors have worked out the idea of setting up scientific and education complexes and developing education districts in the country. This approach meets the objective of improving the quality of higher education in the regions of the country by establishing clear links with regional universities in the most “advanced” areas, organizing scientific and educational activities.Creating education districts serves as the foundation of building up a multicultural education space of the Russian Federation, the resource of lining up control at the federal and regional levels, the formation of a new vector of education policy focused on the preservation and development of a unified, internally differentiated scientific and education space of the country.